(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A present study was undertaken to understand the impact of Piperine and some of its derivatives on the bioavailability of verapamil used in the treatment of cardiac disorders. On oral administration, it undergoes fast biotransformation resulting in its low bioavailability. Its bioavailability varies between 20 % and 35 %. Piperine (a well-known bioenhancer) has been reported to improve the bioavailability of a wide range of structurally and therapeutically varied medicines. Hence some derivatives of piperine were synthesized and evaluated for their bioenhancing effect on verapamil. The bioenhancing effect of piperine and synthesized derivatives was investigated and compared using a validated HPLC method as per the USFDA guidelines. The pharmacokinetic characteristics of verapamil alone and when combined with piperine and its synthetic analogs were also investigated. When administered to Wistar rats, it was discovered that the bioavailability of verapamil was 1.54 times higher when given with piperine and it was 2.42 times higher when given with morpholine derivative. The study undertaken indicates that some synthetic derivatives of piperine can be successfully used to enhance the bioavailability of verapamil to a considerable extent.